Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s00374-019-01374-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of sieving and sample storage on soil respiration and its temperature sensitivity (Q10) in mineral soils from Germany

Abstract: Knowledge about spatial patterns of soil respiration (SR) and its temperature sensitivity (Q10) is of emerging relevance for assessing carbon fluxes across the landscape. Related experiments are often conducted under controlled laboratory conditions and usually rely on soil samples, which are sieved and stored. Here, we investigated the effect of sieving and storage on SR and Q10. We took 14 samples from different land use types and soil textures. Samples were sieved to 2 mm at field-moist conditions and split… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…It is possible that the physical disturbance during soil sampling could have impacted measured microbial parameters, reducing our sensitivity to detect differences among the treatments. However, previous studies found no effects of sieving field‐moist soils on microbial respiration (Meyer et al 2019), and only minor effects on PLFA composition, with sieving primarily reducing the concentration of the fungal biomarker (18:2ω6,9), likely due to the filamentous nature of fungi making them more susceptible to the disturbance (Petersen and Klug 1994). Despite this, we found that the fungal biomarker was one of the PLFAs that drove separation in the microbial community structure among the field treatments, indicating that the signal driven by the field treatments remained stronger than that potentially introduced by the sampling disturbance.…”
Section: Discussionmentioning
confidence: 88%
“…It is possible that the physical disturbance during soil sampling could have impacted measured microbial parameters, reducing our sensitivity to detect differences among the treatments. However, previous studies found no effects of sieving field‐moist soils on microbial respiration (Meyer et al 2019), and only minor effects on PLFA composition, with sieving primarily reducing the concentration of the fungal biomarker (18:2ω6,9), likely due to the filamentous nature of fungi making them more susceptible to the disturbance (Petersen and Klug 1994). Despite this, we found that the fungal biomarker was one of the PLFAs that drove separation in the microbial community structure among the field treatments, indicating that the signal driven by the field treatments remained stronger than that potentially introduced by the sampling disturbance.…”
Section: Discussionmentioning
confidence: 88%
“…However, accounting for the incubation duration, the soil respiration rates were approximately the same. From this, it can be presumed that sample storage for two years had a minor effect on soil respiration (Meyer, Welp, & Amelung, 2019). Further, the relative differences among sites followed the same trend for both tests, finding that sites with lower respiration measurements prior to storage were still lower following storage.…”
Section: Resultsmentioning
confidence: 99%
“…Although standard sieving and storage/freezing procedures can preserve functions, such as microbial respiration, for up to seven weeks (Meyer et al 2019), modifications and stricter measurement timelines may be necessary to limit confounding effects of storage on other soil functions and their temporal dynamics. In this study, longer storage times prior to Microresp experiments may have influenced functional diversity measurements through driving metabolic shifts toward carboxylic acids and recalcitrant organic matter (Goberna et al 2005).…”
Section: Climate Effects More Detrimental In Extensive Meadows and Pasturesmentioning
confidence: 99%